Genetic Variability of Streptococcus mutans and their association with Caries - Carletto Körber, Fabiana Pia Marina (2021)
Fil: Carletto Körber, Fabiana Pia Marina. Universidad Nacional de Córdoba. Cátedra de Odontopediatria A. Facultad de Odontología; Argentina.